2018
DOI: 10.1002/jpen.1171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Muscle Quantity and Quality in Colorectal Cancer Patients: A Propensity Score Matching Analysis

Abstract: Preoperative myopenia could be useful for perioperative management, and quantification of preoperative skeletal muscle mass could identify patients as a high risk for perioperative and oncological outcomes in CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 37 publications
3
48
1
10
Order By: Relevance
“…Further information is described in the Supplementary Materials and Methods. Furthermore, low PMI (myopenia) and high IMAC (myosteatosis) occurred more readily in female patients than in male patients, as previously described …”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…Further information is described in the Supplementary Materials and Methods. Furthermore, low PMI (myopenia) and high IMAC (myosteatosis) occurred more readily in female patients than in male patients, as previously described …”
Section: Methodssupporting
confidence: 74%
“…Furthermore, low PMI (myopenia) and high IMAC (myosteatosis) occurred more readily in female patients than in male patients, as previously described. 22…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of sarcopenia in metastatic cancer patients is well documented. 13,26 Although several factors, such as anorexia due to organ dysfunction by distant metastasis, adverse effect of systemic chemotherapy, deterioration of physical activity, and psychological factors for disease development, can induce sarcopenia in patients, emerging evidence has suggested that sarcopenia may develop because of secretory products from metastatic tissues in various malignancies. 10, 44 Waning and co-workers established seven different mouse models of human osteolytic bone metastases and reported impaired muscle dysfunction in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐operative CT scan images were stored in an electronic format suitable for image analysis to assess the BC status. Using pre‐operative plain CT at superior aspect of the fourth lumbar vertebra as previously described, we measured the cross‐sectional area of the bilateral psoas muscles by manual tracing, and then the psoas muscle mass index (PMI) was calculated as follows: PMI = cross‐sectional area of bilateral psoas muscle∕height 2 (cm 2 /m 2 ). Low PMI was regarded as a proxy for low muscle volume, as previously described .…”
Section: Methodsmentioning
confidence: 99%